Data-Driven Marketing Strategy to Reach Millennial Consumers - Putu Saroyini Piartrini; PA Andiena Nindya Putri; Djoko Widagdo; Ansir Launtu; Sauri Sauri (Dinasti Publisher, 2024)
This article explores the efficacy of data-driven marketing strategies in targeting millennial consumers, a demographic known for its unique preferences and digital savvy. Through a comprehensive literature review, various aspects of data-driven marketing, including customer segmentation, personalized content creation, and omnichannel integration, are analyzed in the context of reaching and engaging with millennials. The review encompasses studies on consumer behavior, digital marketing trends, and data analytics techniques relevant to understanding millennial preferences and behavior. Key findings highlight the importance of data accuracy, privacy considerations, and the role of technology in enhancing marketing effectiveness. Insights from successful case studies and industry best practices provide actionable recommendations for businesses aiming to optimize their marketing efforts towards millennials. This research contributes to the evolving field of data-driven marketing by offering a synthesized understanding of strategies that resonate with the millennial cohort, ultimately fostering long-term brand loyalty and competitive advantage.